2017
DOI: 10.1007/s11661-017-4325-1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ultrasonic Melt Treatment on Macro-Segregation and Peritectic Transformation in an Al-19Si-4Fe Alloy

Abstract: It is well documented that ultrasonic melt treatment (USMT) can refine dendritic and eutectic microstructures during solidification, but much less attention has been paid to the effect of USMT on macro-segregation and intermetallic transformations. In this research, macrosegregation and primary Fe-containing intermetallic peritectic transformations in an Al-19 wt pct Si-4 wt pct Fe alloy were investigated without and with USMT. Macrostructural examination showed that in the absence of USMT the ingot revealed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 50 publications
4
17
0
Order By: Relevance
“…These particles are formed as primary phases in the range of temperatures from 873 K to 888 K (600°C to 615°C) to 853 K (580°C) either directly for the melt or as a product of peritectic reaction with the d (AlFeSi) phase [26,27] and, hence, are subjected to the same refinement mechanisms as primary Si. These results agree well with the reported refinement of the b-Al 5 FeSi particles upon USP performed in the temperature range 983 K to 958 K (710°C to 685°C), [19] 973 K to 883 K (700°C to 610°C) [14] , or 973 K to 873 K (700°C to 600°C…”
Section: A Microstructure Refinement and Modificationsupporting
confidence: 92%
See 1 more Smart Citation
“…These particles are formed as primary phases in the range of temperatures from 873 K to 888 K (600°C to 615°C) to 853 K (580°C) either directly for the melt or as a product of peritectic reaction with the d (AlFeSi) phase [26,27] and, hence, are subjected to the same refinement mechanisms as primary Si. These results agree well with the reported refinement of the b-Al 5 FeSi particles upon USP performed in the temperature range 983 K to 958 K (710°C to 685°C), [19] 973 K to 883 K (700°C to 610°C) [14] , or 973 K to 873 K (700°C to 600°C…”
Section: A Microstructure Refinement and Modificationsupporting
confidence: 92%
“…In addition, the acoustic streaming was shown to distribute primary intermetallics more uniformly in the treated volume. [14] Grain refinement upon USP has been demonstrated on a number of Al-based hypo-eutectic alloys. [11,15] For near-eutectic Al-Si alloys, the refinement of primary Si and some intermetallics have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Gas pores usually exhibits round shape. this phenomenon also can be found in Refs [8][9][10][11][12]41]. The enlarged 3D morphology of shrinkage and gas pores are clearly observed in Fig.…”
Section: Effect Of Usp On the 3d Microstructure Of The Alloyssupporting
confidence: 76%
“…It has been reported that the narrow size distribution of refiner particles after UST of Zr added to Mg [6] and Al-Ti-B [67], Al-Zr, Al-Zr-Ti [63] added to Al alloys results in better grain refinement. The refinement of blocky and needle shape primary intermetallic phases such as Al 3 Ti [63,68], Al 3 (Zr, Ti) [63,69], primary Si [70,71,72] and β/δ-Al-Fe-Si [24,25] phases is an added advantage of UST that further improves the mechanical properties of the cast alloys. Figure 7 shows a summary of the common intermetallic phases encountered in commercial Al alloys and their refinement after UST.…”
Section: Ust Applied To the Liquid Meltmentioning
confidence: 99%
“…Liquid and semi-solid melt processing with power ultrasound has received considerable attention and has been successfully demonstrated for the refinement of as-cast grain structure in light alloys without the need for grain refiners, therefore eliminating the limitations associated with inoculation processes for Al and Mg based alloys [20,21,22]. The benefits of ultrasonic treatment (UST) include the production of non-dendritic structures, degasification and the refinement of primary phases (Al 3 Zr, Al 3 Ti, Al-Fe-Si and primary Si) [23,24,25]. This technique has attracted commercial interest due to being environmentally friendly, cost effective and possesses several technical advantages over conventional methods in molten metal processing [23,26,27].…”
Section: Introductionmentioning
confidence: 99%